Foliar water uptake enables embolism removal in excised twigs of Avicennia marina. Issue 4 (7th December 2022) - Fuenzalida, Tomás I.; Blacker, Matthew J.; Turner, Michael; Sheppard, Adrian; Ball, Marilyn C.
Summary: Embolism refilling is thought to require relaxation of xylem tension, and it is unclear whether and how tall trees or plants growing in arid or saline soils recover from embolism. We tested whether foliar water uptake could enable embolism refilling in dehydrated twigs of the grey mangrove ( Avicennia marina ). Four dehydrated twigs were imaged by laboratory‐based micro‐computed tomography before and after wetting leaves. Emboli were observed in dehydrated stems and leaves. Embolism decreased with increasing distance from the cut end of stems, suggesting that stem emboli were caused by cutting. A significant ( P = 0.026) c . 80% reduction in the embolised area was observed in leaves between the start and the end of the experiment (29 ± 10 h after wetting). Embolus diameter was unaffected by wetting. Embolism refilling occurred slowly, in stems embolised by cutting and leaves embolised by cutting and/or dehydration. The lack of response of embolus diameter to wetting suggests that capillarity was not the main mechanism for refilling. Results show that excised twigs of A . marina are able to recover from embolism by absorption of atmospheric water and call for studies under natural conditions.